The Journal of Sarah Haynsworth Gayle, 1827-1835 : A Substitute for Social Intercourse - Gayle, Sarah Ann Haynesworth, 1804-1835 (Book collections on Project MUSE., 2013)
Astonishing, tragic, and remarkable, the journal of Sarah Haynsworth Gayle, wife of early Alabama governor John Gayle, is among the most widely studied and seminal accounts of antebellum life in the American South. This is the first complete edition of the journal in print. Bereft of the companionship of her often-absent husband, Sarah considered her journal "a substitute for social intercourse" during the period from 1827 to 1835. It became the social and intellectual companion to which she confided stories that reflected her personal life and the world of early Alabama. Sarah speaks directly to us of her loneliness, the challenges of child rearing, her fear of and frustration with the management of slaves, and the difficulty of balancing the responsibilities of a socially prominent woman with her family's slender finances. The poor condition of the journal and its transcripts, sometimes disintegrated or reassembled in the wrong order, has led historians to misinterpret Gayle's words. Gayle's descendants, Alabama's famed Gorgases, deliberately obscured or defaced many passages. Using archival techniques to recover the text and restore the correct order, the editors reveal the unknown story of Sarah's economic hardships, the question of her husband's "temperance," and her opium use.